THE IMPACT OF APPLYING ENVIRONMENTAL MANAGEMENT ON THE PERFORMANCE OF EMPLOYEES: AN APPLIED STUDY ON THE EMPLOYEES OF AL-QASIM GREEN UNIVERSITY (World Bulletin of Management and Law, 2022)
The research aims to identify the reality of environmental management and the performance level of employees at Al-Qasim Green University, as well as to identify the impact and relationship between applying environmental management and the performance of employees at Al-Qasim Green University. The researchers used a descriptive approach using the survey method, due to its relevance to the nature and objectives of the research. The research community consisted of the heads of departments at Al-Qasim Green University. 39 respondents participated in this research, representing the various departments at Al-Qasim Green University, and the sample represented 100%. The sources of data collection were questionnaires, the measurement tool distributed to the first research sample